فعالية برنامج تدريبي قائم على التعلم المدمج لتنمية مهارات القرن الحادي والعشرين التدريسية لدى معلمي الدراسات الاجتماعية - السحت، مصطفى زكريا أحمد (جامعة القاهرة - كلية الدراسات العليا للتربية, 2021)
هدف البحث الحالي إلى تعرف فعالية برنامج تدريبي قائم على التعلم المدمج لتنمية مهارات القرن الحادي والعشرين التدريسية لدى معلمي الدراسات الاجتماعية، وتم استخدام كلًا من المنهج الوصفي وذلك للاستفادة من أدبيات البحث التربوي في مجال التعلم المدمج ومهارات القرن الحادي والعشرين في صياغة الإطار النظري وإعداد أدوات البحث، وكذلك المنهج شبه التجريبي القائم على تطبيق البرنامج التدريبي المقترح على عينة البحث المكونة من (٤٩) معلم ومعلمة من معلمي الدراسات الاجتماعية، وقد أعد الباحث مقياسًا لقياس مهارات القرن الحادي والعشرين التدريسية لدى المعلمين. وقد أظهرت النتائج وجود فروق ذات دلالة إحصائية بين أفراد العينة في مهارات القرن الحادي والعشرين التدريسية لصالح التطبيق البعدي، كما أظهرت وجود فروق ذات دلالة إحصائية بين المعلمين والمعلمات في مهارة (الثقافة الرقمية، الاتصال الفعال، الإنتاجية العالية) ومهارات القرن الحادي والعشرين التدريسية ككل تعزى لمتغير الجنس ولصالح المعلمات. بينما لا توجد فروق بين المعلمين والمعلمات في مهارة التفكير الخلاق كأحد مهارات القرن الحادي والعشرين التدريسية تعزى لمتغير الجنس. The current research aimed at identifying the effectiveness of a training program based on blended learning to develop the teaching skills of the twenty-first century among teachers of social studies. Both the descriptive approach was used in order to benefit from the literature of educational research in the field of blended learning and twenty-first century skills in formulating the theoretical framework and preparing research tools, as well as the quasi-experimental approach based on the application of the proposed training program on the research sample consisting of (49) male and female teachers. Social Studies, the researcher has prepared a scale to measure the twenty-first century teaching skills of teachers. The results showed that there are statistically significant differences between the respondents in the twenty-first century teaching skills in favor of the post application, It also showed that there are statistically significant differences between male and female teachers in the skill (digital culture, effective communication, high productivity) and the twenty-first century teaching skills as a whole due to the gender variable and in favor of the female teachers. While there are no differences between male and female teachers in the creative thinking skill as one of the twenty-first century teaching skills due to the gender variable.
Keywords: التعلم المدمج -- المهارات التدريسية -- البرامج التدريبية -- السعودية